SleepSure: a pilot randomized-controlled trial to assess the effects of eye masks and earplugs on the quality of sleep for patients in hospital. (February 2019) - Sweity, Samaher; Finlay, Andrew; Lees, Charlotte; Monk, Adam; Sherpa, Toshi; Wade, Derick
Objective: To determine the short-term effects of supplying hospital inpatients with earplugs and eye masks, preparatory to a full-scale trial. Design: A single-centre, open-label, two-arm, parallel group, randomized-controlled trial. Setting: A total of 13 medical and surgical wards in a large teaching hospital in the United Kingdom. Participants: Everyone admitted to hospital aged 18 years or older, who stayed overnight and had the mental capacity and sufficient understanding of English to give consent, the ability to complete the study questionnaire and the ability to use earplugs and eye masks unaided was considered. Interventions: The intervention group was provided with earplugs and eye masks for use the following night, and the control group received standard care. Main measures: Sleep quality assessed using the SleepSure questionnaire after the first night of using the intervention, use of earplugs and eye masks, number of falls throughout their inpatient stay, use of zopiclone during inpatient stay, length of stay and recruitment rate. Results: A total of 1600 patients were admitted; out of which, 626 (39%) were eligible and 206 (13% total, 33% eligible) recruited (intervention group, 109). The intervention group's mean sleep quality score was 6.33 (95% confidence interval (CI): 5.89–6.77), compared with 5.09 (95% CI: 4.66–5.52) in the control group ( p < 0.001). There were no differences in use of zopiclone, falls or length of stay between the groups. Of the intervention group, 91 (86%) reported using the earplugs and/or eye masks. Conclusions: The intervention seems feasible, and effective, but trial eligibility rate and rate of recruitment into the study were limited.